Analysis of laboratory blood parameter results for patients diagnosed with COVID‐19, from all ethnic group populations: A single centre study. (3rd May 2021) - Marwah, Mandeep; Marwah, Sukhjinder; Blann, Andrew; Morrissey, Hana; Ball, Patrick; Wandroo, Farooq A.
Abstract: Introduction: Although factors such as age, sex, diabetes, obesity and changes in certain laboratory investigations are important prognostic factors in COVID‐19 infection, these may not apply to all ethnic/racial groups. We hypothesized differences in routine biochemistry and haematology indices in Caucasian and a combined group of Black, Asian and Minority Ethnic (BAME) patients who tested positive for COVID‐19 who died, compared to survivors. Methods: We tested our hypothesis in 445 patients (229 Caucasian, 216 BAME) admitted to secondary care with proven COVID‐19 infection, in whom standard routine laboratory indices were collected on admission. Results: After 28 weeks, 190 (42.7%) had died within 28 days of COVID diagnosis (97 Caucasians [42.4%], 93 BAMEs [43.1%], P  = .923). A general linear model analysis found the ethnicity interaction with mortality to be significant for fibrinogen, ferritin and HbA1 c (after controlling for age). In a multivariate analysis, a neutrophil/lymphocyte ratio > 7.4 and a urea/albumin ratio > 0.28 increased the odds of death for both the Caucasian and the BAME group. Additional factors increasing the odds ratio in the BAME group included age >60 years and being diabetic. Conclusion: Neutrophil/lymphocyte ratio and urea/albumin ratio are simple metrics that predict death to aid clinicians in determining the prognosis of COVID‐19 and help provide early intensive intervention to reduce mortality. In the BAME groups, intensive monitoring even at younger age and those with diabetes may also help reduce COVID‐19 associated mortality.